Author Correction: Blunting neuroinflammation with resolvin D1 prevents early pathology in a rat model of Parkinson’s disease - Krashia, Paraskevi; Cordella, Alberto; Nobili, Annalisa; La Barbera, Livia; Federici, Mauro; Leuti, Alessandro; Campanelli, Federica; Natale, Giuseppina; Marino, Gioia; Calabrese, Valeria; Vedele, Francescangelo; Ghiglieri, Veronica; et al. (Nature communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.